Wolność egoisty - Cielecki, Paweł (Acta Universitatis Lodziensis. Folia Philosophica. Ethica-Aesthetica-Practica, 2008)
The main purpose of this article is to outline the idea of the anarchistic egoism included in Max Stirner's "Ego and His Own". I tried to represent Stirner as an original philosopher who visibly distinguished himself among other thinkers of his days. My aim was also defend him from various attacks of his critics and adversaries who reproached him for being inconsistent or perplexed in the very vulnerable spots of his work. In my opinion 'being awkward' which Camus accuses Stirner of, is nothing else than a tough consequence of the egoistic philosophy which forced the author of "Ego and His Own" to stop his deduction in some point. By referring to Nietzsche and existentialists I endeavoured to show Stirner's Egoist as a precursor of the Nietzsche's Superman and the Camus's Stranger. In the evolution of an idea this two directions were two different ways of extending the construction which foundations were laid down by Stirner. That is why I find Max Stirner one of the most influential thinker of the 10th century who had a great impact on formation of the new look on man and his world. This article is about solitude, alienation, egoism, strength and power which born every time when the conscious and sovereign human being is faced with the indifferent, trivial and inert world.